A review on the emerging role of SIRT6 in cardiovascular diseases - Dinar, Md. ShahOwaly Ullah (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.